Tác động của hình ảnh điểm đến, giá trị cảm xúc tới sự hài lòng và lòng trung thành của du khách đến thành phố Đà Lạt - Phan Minh, Đức; Lê Tấn, Bửu (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
This research analyzes the impacts of destination image and emotional value on the satisfaction and loyalty of tourists visiting Dalat City. The questionnaire survey is used to collect the data in addition to multivariate analysis methods (e.g., Cronbach Alpha test, EFA, CFA, SEM) employed to analyze the data obtained. The analysis results from 503 tourists in Dalat show that destination image and emotional value directly affect the satisfaction and indirectly affect the loyalty of these tourists. Policy makers, as well as tourism businesses in Dalat City, are accordingly suggested to establish local tourism brands contingent on tourists' perception of potential destinations for sustainable development.
Keywords: Destination image; Emotional value; Satisfaction; Loyalty